Uncovering the ethnobotanical importance of community forests in Chai Nat Province, Central Thailand - SUKANDA CHAIYONG; WITTAYA PONGAMORNKUL; PRATEEP PANYADEE; ANGKHANA INTA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Chaiyong S, Pongamornkul W, Panyadee P, Inta A. 2023. Uncovering the ethnobotanical importance of community forests in Chai Nat Province, Central Thailand. Biodiversitas 24: 2052-2063. Ethnobotanical studies are crucial for understanding local communities' traditional knowledge and use of plants and conserving biodiversity. This is the first public ethnobotanical study in the Chai Nat Province. It is an essential contribution to the limited knowledge of the traditional use of plants in this region. Three key informants with high experience in traditional knowledge were selected through a small meeting in the village. Using a semi-structured interview method during the walk-to-the-wood method, we gathered data on 103 plant species belonging to 92 genera and 49 families. The majority of the plant species (57) were used for medicinal purposes, followed by food (38), materials (17), and other small categories. It is worth noting that some plant species were used in more than one category. Our study provides an in-depth understanding of local communities’ traditional knowledge and use of plants which is essential for managing and conserving these important resources. This study not only contributes to the field of ethnobotany but also highlights the importance of preserving traditional ecological knowledge for future generations.